Development and validation of a prognosis risk score model for neonatal mortality in the Amhara region, Ethiopia. A prospective cohort study - Mengstu Melkamu Asaye; Yohannes Hailu Matebe; Helena Lindgren; Kerstin Erlandsson; Kassahun Alemu Gelaye (Global Health Action)
Background A neonatal mortality prediction score can assist clinicians in making timely clinical decisions to save neonates’ lives by facilitating earlier admissions where needed. It can also help reduce unnecessary admissions. Objective The study aimed to develop and validate a prognosis risk score for neonatal mortality within 28 days in public hospitals in the Amhara region, Ethiopia. Methods The model was developed using a validated neonatal near miss assessment scale and a prospective cohort of 365 near-miss neonates in six hospitals between July 2021 and January 2022. The model’s accuracy was assessed using the area under the receiver operating characteristics curve, calibration belt, and the optimism statistic. Internal validation was performed using a 500-repeat bootstrapping technique. Decision curve analysis was used to evaluate the model’s clinical utility. Results In total, 63 of the 365 neonates died, giving a neonatal mortality rate of 17.3% (95% CI: 13.7–21.5). Six potential predictors were identified and included in the model: anemia during pregnancy, pregnancy-induced hypertension, gestational age less than 37 weeks, birth asphyxia, 5 min Apgar score less than 7, and birth weight less than 2500 g. The model’s AUC was 84.5% (95% CI: 78.8–90.2). The model’s predictive ability while accounting for overfitting via internal validity was 82%. The decision curve analysis showed higher clinical utility performance. Conclusion The neonatal mortality predictive score could aid in early detection, clinical decision-making, and, most importantly, timely interventions for high-risk neonates, ultimately saving lives in Ethiopia.